2015
DOI: 10.1016/j.virol.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Sequence specificity for uridylylation of the viral peptide linked to the genome (VPg) of enteroviruses

Abstract: Enteroviruses (EV) uridylylate a peptide, VPg, as the first step in their replication. VPgpUpU, found free in infected cells, serves as the primer for RNA elongation. The abilities of four polymerases (3Dpol), from EV-species A-C, to uridylylate VPgs that varied by up to 60% of their residues were compared. Each 3Dpol was able to uridylylate all five VPgs using polyA RNA as template, while showing specificity for its own genome encoded peptide. All 3Dpol uridylylated a consensus VPg representing the physical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…This reaction uses the normal 3D pol active site in a macromolecular complex where the VPg tyrosine hydroxyl is presumably positioned in the active site to mimic a RNA 3′ hydroxyl group. In vitro uridylylation is possible using a mixture of 3D pol , VPg, poly(A) RNA, and UTP, and for this reaction there is significant cross-reactivity between different viral 3D pol and VPg proteins (Schein et al, 2015). However, uridylylation is much more efficient with cre RNA and 3CD pro as cofactors to form a complex with a significantly lower K m for UTP (Paul et al, 2000; Steil and Barton, 2008; Yin et al, 2003).…”
Section: 3dpol–vpg Complexesmentioning
confidence: 99%
“…This reaction uses the normal 3D pol active site in a macromolecular complex where the VPg tyrosine hydroxyl is presumably positioned in the active site to mimic a RNA 3′ hydroxyl group. In vitro uridylylation is possible using a mixture of 3D pol , VPg, poly(A) RNA, and UTP, and for this reaction there is significant cross-reactivity between different viral 3D pol and VPg proteins (Schein et al, 2015). However, uridylylation is much more efficient with cre RNA and 3CD pro as cofactors to form a complex with a significantly lower K m for UTP (Paul et al, 2000; Steil and Barton, 2008; Yin et al, 2003).…”
Section: 3dpol–vpg Complexesmentioning
confidence: 99%
“…Previous work showed that the CVA24 3D pol can uridylylate VPg peptides from even very distantly related EV 28 . As Figures 3 and 5 indicate, it is a very active protein.…”
Section: Discussionmentioning
confidence: 99%
“…CVA24 and the PCP consensus VPgs were synthesized and CVA24 3D pol and Dengue virus (DENV) NS5 polymerase (used for control assays not shown) were purified as described elsewhere 28, 35 . The CVA24 polymerase was concentrated to about 3 mg/ml and stored at −20°C in PB with additional glycerol added to a final concentration of 18%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations